'The Moustache Makes Him More of a Man': Waiters' Masculinity Struggles, 1890–1910. (14th February 2019) - Eyben, Rosalind
Abstract: When moustaches were at the height of European fashion among men of all classes, why did luxury restaurants require their waiters to be clean-shaven and why did some waiters object? The article draws primarily on the contemporary press to examine the ambivalent gender and class position of waiters who did a 'woman's job' and dressed like a gentleman to perform extreme subservience for rich men's enjoyment. The moustache ban was an exercise of power over the waiter beyond the workplace into other domains. It embodied the innate subservience of the domestic servant and reinforced the perception of the public, including fellow trade unionists, that waiters were emasculated feudal retainers rather than manly men earning their living in the modern market place. Waiters were the butt of jokes. In Britain, the Trades Union Congress laughed at their union's claims to the moustache and finally in 1899 told them to stay away. Waiters' servile direct dependence on the wealthy was a threat to a working-class masculinity of independence and hard physical work. As the waiters' leader well understood, their lack of moustache served to confirm the general perception that waiters were neither real workers nor real men.